Cross-sectional associations of objectively assessed sleep duration with physical activity, BMI and television viewing in German primary school children - Susanne Kobel; Olivia Wartha; Jens Dreyhaupt; Sarah Kettner; Jürgen M. Steinacker (BMC, 2019)
Abstract Background The global incidence of overweight and obesity has increased dramatically among children and adolescents over the past decades. Insufficient sleep duration and physical inactivity are known risk factors for overweight and obesity in children. To engage children in a healthier lifestyle knowledge about associations of sleep duration and behavioural aspects in children are vital. Therefore, this study investigated the mentioned associations in German primary school children. Methods Data of 308 first and second graders (7.1 ± 0.6 years) was used; children's anthropometric data were taken during a school visit. Children's physical activity (PA) and sleep duration were assessed objectively (Actiheart©, CamNtech Ltd., Cambridge, UK); children's daily television time and socio-demographic data were collected via parental questionnaire. Linear mixed-effects regression models as well as logistic regressions were used to determine associations of PA, television viewing, age, gender, BMI z-scores and socio-economic variables on sleep duration. Results In linear regression models young age and not having a migration background were significantly associated with long sleep duration (p < 0.001). In logistic regressions, long night time sleep (≥10:08 h; compared to medium and short sleep duration) was significantly associated with not reaching the PA guideline (OR 0.60 [0.36;0.99]), daily television viewing of less than one hour (OR 0.44 [0.24;0.80]), young age (OR 0.38 [0.21;067]), a high parental education level (OR 0.52 [0.27;0.99]) and the lack of migration background (OR 0.21 [0.10;0.48]). However, if controlling for age, gender, parental education level and migration background, reaching the PA guideline stayed no longer significantly associated with a tertiary sleep level. Conclusions Children in the highest sleep category showed a negative association with reaching the PA guideline and a positive association with daily television viewing. This therefore adds to previously primarily subjectively assessed associations of sleep and risk factors for obesity (related behaviours) with a detailed insight based on objective data. Hence, interventions trying to decrease children's BMI and television viewing should also aim at extending children's night-time sleep and inform parents about the importance of sufficient sleep during childhood. Trial registration DRKS-ID: DRKS00000494.